A new species of the spider genus Taczanowskia (Araneae, Araneidae) from Mexico - Ibarra-Núñez, Guillermo (Zootaxa, 2013)
A new species of the spider genus Taczanowskia, T. gustavoi n. sp. is described from Chiapas, Mexico. This finding ex-tends the distribution of Taczanowskia species, hitherto known only from South America to Southern Mexico. T. gustavoi n. sp. can be differentiated from all other species in this genus by having more than six tubercles in the dorsum of its opist-hosoma. This species is included in an earlier determination key for all previously known Taczanowskia species.